A revision of the genus Calcigorgia (Cnidaria, Octocorallia, Acanthogorgiidae) with the description of three new species - Matsumoto, Asako K.; van Ofwegen, Leen P.; Bayer, Frederick M. (Zootaxa, 2019)
Octocorals of the Acanthogorgiid genus Calcigorgia have been examined, from Japan, Sea of Okhotsk, and Bering Sea. The four known species are re-described and scanning electron microscopy (SEM) images of sclerites presented. Three other species are described and depicted, bringing the total number of Calcigorgia species to seven. Calcigorgia simushiri, Dautova 2018 is synonymized with C. spiculifera Broch, 1935. A neotype for C. spiculifera has been designated.